The Effectiveness of Administrative Sanctions in Promoting Legal Compliance in Indonesian Legislation - Dedy Suwandi; Wafda Vivid Izziyana (Sabtida, 2026)
Administrative sanctions play an important role in promoting legal compliance within Indonesian administrative law, yet their effectiveness remains limited due to inconsistencies between normative design and enforcement practice. This study addresses the need for a more systematic understanding of administrative sanctions by examining their normative structure across sectors and evaluating their practical implementation. The research adopts a socio-legal approach that prioritizes normative legal analysis, supported by limited empirical insights from interviews and secondary legal materials. The analysis is guided by a theoretical framework that integrates legal substance, institutional structure, and legal culture. The findings show that administrative sanctions are formally structured through a graduated model, but their application is often inconsistent, with weak escalation, limited monitoring, and fragmented institutional coordination. As a result, sanctions tend to function symbolically rather than as effective instruments of compliance. The study proposes a theoretical model of administrative sanction effectiveness based on the alignment of normative coherence, institutional capacity, and enforcement legitimacy. Strengthening this alignment is essential for transforming administrative sanctions into reliable tools of regulatory governance and achieving sustainable legal compliance.